A história e cultura africana e afro-brasileira (Lei 10639/03) em Mato Grosso : aulas oficinas e didática da História - Siqueira, Pryscila Aparecida Moreira Salgado (2020)
This research aims to analyze African and Afro-Brazilian history and culture using the textbook. To this end, the textbook of the 8th year of Elementary Education from the Historiar collection will be analyzed, by the author Gilberto Cotrim and Jaime Rodrigues of the PNLD 2017 - 2019, 2nd edition of Saraiva publisher, chosen by the State School Djalma Ferreira de Souza (2017- 2019 ). The definition of the textbook as a propellant of research is due to its use by History professionals as a historical source and didactic resource in the classroom. From the analysis of the textbook, one can investigate the gaps, silences, stereotypes, images and texts presented about African and Afro Brazilian cultural groups. Theoretically, the research is based on the studies of Kabenguele Munanga (2005), Nilma Lino Gomes (2012) and Angela Davis (2013), on issues related to Africanity. On the workshops classes, the approaches of Isabel Barca and Jörn Rüsen are used, in addition to the basis of Law 10.639 / 2003 with the Racial Ethnic Curricular Guidelines. About the textbook, we base our research on Alain Choppin and Sonia Regina Miranda and Tania Regina Luca. And to propose workshops classes with historical themes related to African and Afro-Brazilian history and culture that are in line with the Curricular Guidelines of Mato Grosso that can contribute to the students' historical learning and in the implementation of Law 10.639 / 03, bringing a positive view of the afro population.